Yeast Culture Improves Egg Quality and Reproductive Performance of Aged Breeder Layers by Regulating Gut Microbes - Liu, Yuchen; Cheng, Xue; Zhen, Wenrui; Zeng, Dan; Qu, Lujiang; Wang, Zhong; Ning, Zhonghua (Frontiers in Microbiology, 2021)
The purpose of this study was to investigate the effects of dietary yeast culture (YC) supplementation on egg production, egg quality, reproductive performance, immune functions, antioxidant capacity and intestinal microbial structure of aged hens. A total of 224 Hy-Line Brown layers (54 weeks) were randomly assigned into 2 dietary treatments including control group fed basal diet (DC) and the YC group supplemented with YC at 2.0 g /kg of diet. Each group has 7 replicates with 16 hens each. The study was lasted 8 weeks. The results showed that YC addition has no significant effect on production performance, however, the addition of YC can significantly improve the egg quality and hatching rate, enhance the digestibility of ileum crude fat, increase the serum parameters of lysozyme and T-AOC activity (P<0.05), while reduce serum AST level (P< 0.05). 16S rRNA analysis showed that the addition of YC significantly altered the ileum microbial composition. The LEfSe analysis showed that Bacilli and Lactobacillales were significantly enriched in the YC group. PICRUSt analysis of the ileal microbiota found that such as Glutathione metabolism, ubiquinone and other terpenoid-quinone biosynthesis and lipopolysaccharide biosynthesis proteins pathways were highly enrichment in YC group as compared to DC group. To sum up, the addition of YC can improve egg quality, immune functions, antioxidant capacity, reproduction efficiency and digestive absorption, possibly through enriching the abundance of Lactobacillales and Bacilli meanwhile improving the biosynthesis of lipopolysaccharide proteins, glutathione metabolism and the synthesis of ubiquinone and other terpenoids-quinone metabolic pathway.